The Versatile Type V CRISPR Effectors and Their Application Prospects - Tong, Baisong; Dong, Huina; Cui, Yali; Jiang, Pingtao; Jin, Zhaoxia; Zhang, Dawei (Frontiers in Cell and Developmental Biology, 2021)
The class II clustered regularly interspaced short palindromic repeats (CRISPR)–Cas systems, characterized by a single effector protein, can be further subdivided into types II, V, and VI. The application of the type II CRISPR effector protein Cas9 as a sequence-specific nuclease in gene editing has revolutionized this field. Similarly, Cas13 as the effector protein of type VI provides a convenient tool for RNA manipulation. Additionally, the type V CRISPR–Cas system is another valuable resource with many subtypes and diverse functions. In this review, we summarize all the subtypes of the type V family that have been identified so far. According to the functions currently displayed by the type V family, we attempt to introduce the functional principle, current application status, and development prospects in biotechnology for all major members.